Study on the mechanism of enlarged spherulite diameter for aliphatic polyester ionomers. (19th April 2022) - Li, Xiangyu; Ru, Ke; Zhang, Shuidong; Chen, Yu-Kun
Abstract: Aliphatic polyesters with repeated chemical cycle performance are the promising candidate to eliminate environment pollution evoked by the petroleum-based plastics. The incorporation of ionic group can improve the strength, thermal resistance and melt viscosity of polyesters and promote them to utilize at high performance film or foam. Interestingly, these semi-crystalline ionomers achieve significant enlarged spherulite diameter (Du ) when the content of ionic group is 0.58 mol%. To explore the unexpected phenomenon, poly(ethylene succinate) and poly(decamethylene succinate) phosphorus-containing ionomers (PESIs-K and PDSIs-K) with 0.58–1.91 mol% ionic group containing phosphorus (PCIG) were prepared by condensation polymerization of ethylene glycol (or 1, 10-decamethylene glycol), succinic acid and phosphorous ion monomers (DHPPO-K), respectively. The effects of PCIG content and types of diols on the chemical structures, thermal behavior, crystallization, and rheological behavior of samples were characterized by FTIR, NMR, DSC, POM, XRD, SAXS, DMA and rotational rheometer, respectively. Strikingly, the t 1/2 of PESI1-K decreased from 7.0 to 2.9 min, while its Du increased from 103 to 171 μm. The reasons were that PESI1-K with moderate heterogeneous nucleation sites and melt viscosity guaranteed it to achieve high crystal growth rate, and enough growth time and space for each grain. Moreover, the incorporation of electrostatic interactions by ionic clusters facilitated the crystalline grains to cumulate in large spherulites without collapse. However, due to the improved flexibility, the relaxation time of PDS and its ionomers were much lower than those of PES and PESIs-K, while their self-nucleation capacity increased, which decreased the Du . Summarily, the effects of PCIG on crystallization behaviors were elaborated in detail and the improved Du mechanism of ionomers was proposed. Graphical abstract: Image 1 Highlights: 0.58 mol% phosphorus-containing ionic groups facilitate the crystallization and enlarge spherulite diameter of PES. The electrostatic interactions by ionic clusters facilitate the crystalline grains to cumulate in large spherulites. The high chain flexibility of decamethylene succinate promotes the crystallization and perfect the crystal of ionomers. The mechanism of enlarged spherulite diameter for PESIs-1 is proposed.